Exploring Adiponectin and Leptin Levels as Potential Biomarkers in Osteoporosis Pathogenesis - Manal F. Al-Khakani; Mundher Mudhafar; Muna Sadeq Hameed (Medical Journal of Babylon)
Background: Accurate and early diagnosis of osteoporosis, a skeletal disorder characterized by low bone density and increased fracture risk, is crucial for effective management. This study aimed to evaluate the diagnostic potential of adiponectin and leptin levels as biomarkers for osteoporosis. Objectives: The primary objective of this study was to investigate whether adiponectin and leptin levels could serve as biomarkers for diagnosing osteoporosis and distinguishing it from healthy individuals. Materials and Methods: A total of ninety participants, including healthy individuals (n = 30) and patients with osteoporosis (n = 30) or osteopenia (n = 30), underwent comprehensive evaluations. Demographic, clinical, hormonal, and lipid profiles were assessed. Additionally, bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry. Enzyme-linked immunosorbent assays were conducted to measure adiponectin and leptin levels in serum samples. Results: Significant differences were observed between osteoporosis patients and healthy controls in several parameters. Osteoporosis patients were older and had a lower body mass index compared to healthy individuals. Furthermore, BMD was significantly lower in osteoporosis patients. Hormonal and lipid profiles also differed significantly between the two groups. Notably, adiponectin levels were lower, whereas leptin levels were higher in osteoporosis patients compared to healthy controls. These findings suggest that adiponectin and leptin levels may have diagnostic potential for osteoporosis. Conclusion: Adiponectin and leptin levels exhibit promise as biomarkers for the accurate diagnosis of osteoporosis and differentiation from healthy individuals. Further research and validation studies are warranted to confirm their utility in clinical practice.